2020
DOI: 10.33160/yam.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients on Home Oxygen Therapy with Telemonitoring

Abstract: Home oxygen therapy (HOT) is an important treatment for patients with chronic respiratory diseases. Recently, telemonitoring of HOT has been become available. In the present study, we examined whether telemonitoring of HOT could improve health-related quality of life (HRQOL). Twelve patients receiving HOT participated in this study. The oxygen flow rates, use of the oxygen concentrator, and the values of percutaneous arterial oxygen saturation measured by each patient with a pulse oximeter were checked using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…20,21 An interventional guidance based on telemonitoring of oxygen concentrator usage conditions, pulse rates, and SpO 2 levels in patients receiving HOT for chronic respiratory failure was reported to improve vitality and mental health scores assessed with the Medical Outcome Study 36-Item Short Form Health Survey (SF-36). 22 In contrast, some studies have found that telemonitoring does not improve HRQOL in patients with COPD. 10,23,24 A systematic review attributed this finding to differences between studies in the methods used for telemonitoring in patients with COPD; specifically, some studies involved simple telemonitoring of biological variables, whereas others used the telemonitoring data to intervene.…”
Section: Effects On Hrqolmentioning
confidence: 96%
“…20,21 An interventional guidance based on telemonitoring of oxygen concentrator usage conditions, pulse rates, and SpO 2 levels in patients receiving HOT for chronic respiratory failure was reported to improve vitality and mental health scores assessed with the Medical Outcome Study 36-Item Short Form Health Survey (SF-36). 22 In contrast, some studies have found that telemonitoring does not improve HRQOL in patients with COPD. 10,23,24 A systematic review attributed this finding to differences between studies in the methods used for telemonitoring in patients with COPD; specifically, some studies involved simple telemonitoring of biological variables, whereas others used the telemonitoring data to intervene.…”
Section: Effects On Hrqolmentioning
confidence: 96%
“…При этом десатурация, которая нередко развивается у таких больных во время нагрузки, быстро исчезает после остановки. N. Burioka et al разработали модифицированный 6-МШТ, результатом которого является не пройденное расстояние, а скорость ходьбы (число шагов в секунду) [13]. Число шагов подсчитывали вручную каждые 5 с тестирования.…”
Section: -минутный шаговый тестunclassified
“…Reduce travel time and frequency of attendance at outpatient clinics [44,82] Patient and healthcare professional acceptance of telemedicine [74,122] More frequent monitoring and contact with patients [48,49] Familiarity with technology [69,114] Reduce caregiver burden [101] Infrastructure costs [123] Improve QoL [40,47,92] Data security and reliability [119,121,122] Reduce attendance at primary care and emergency department [37,38,63,94] High-quality evidence to justify use [4,5,118] Reduce hospitalisations [36,38,63,64,79,94] An increase in workload to monitor large amounts of data [123] Increase patient empowerment with immediate feedback [69] Potential for long-term cost savings [46,87] Opportunity for big data analysis to answer outstanding questions in rare conditions [107] Key points…”
Section: Opportunities Challengesmentioning
confidence: 99%
“…The telemonitoring included remote monitoring use of the oxygen concentrator as well as pulse oximetry. Although summary SF-36 score did not improve, the vitality and mental health sub-scores did improve significantly following the initiation of the programme, suggesting telemonitoring may have a role in the maintenance of QoL in these patients [ 40 ]. Another approach using remote monitoring of oximetry and activity using an accelerometer in patients requiring LTOT was well received, with good patient satisfaction [ 41 ].…”
Section: Use Of Telehealth In Chronic Respiratory Failurementioning
confidence: 99%